Physiological regulation of yeast cell death in multicellular colonies is triggered by ammonia - Váchová, Libuse; Palková, Zdena (The Journal of cell biology, 2005)
The existence of programmed cell death (PCD) in yeast and its significance to simple unicellular organisms is still questioned. However, such doubts usually do not reflect the fact that microorganisms in nature exist predominantly within structured, multicellular communities capable of differentiation, in which a profit of individual cells is subordinated to a profit of populations. In this study, we show that some PCD features naturally appear during the development of multicellular Saccharomyces cerevisiae colonies. An ammonia signal emitted by aging colonies triggers metabolic changes that localize yeast death only in the colony center. The remaining population can exploit the released nutrients and survives. In colonies defective in Sok2p transcription factor that are unable to produce ammonia, death is spread throughout the whole population, thus decreasing the lifetime of the colony. The absence of Mca1p metacaspase or Aif1p orthologue of mammalian apoptosis-inducing factor does not prevent regulated death in yeast colonies.
Keywords: Saccharomyces cerevisiae; Signal Transduction; regulace genové exprese u hub; NADH, NADPH oxidoreduktasy; Ammonia; apoptóza; NADH, NADPH Oxidoreductases; kaspasy; Caspases; Repressor Proteins; Saccharomyces cerevisiae - proteiny; Saccharomyces cerevisiae Proteins; amoniak; signální transdukce; represorové proteiny; Apoptosis; Gene Expression Regulation, Fungal